2015
DOI: 10.3109/08958378.2015.1030481
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial inflammatory transcriptional responses to an altered plasma exposome following inhalation of diesel emissions

Abstract: Background Air pollution, especially emissions derived from traffic sources, is associated with adverse cardiovascular outcomes. However, it remains unclear how inhaled factors drive extrapulmonary pathology. Objectives Previously, we found that canonical inflammatory response transcripts were elevated in cultured endothelial cells treated with plasma obtained after exposure compared with pre-exposure samples or filtered air (sham) exposures. While the findings confirmed the presence of bioactive factor(s) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 70 publications
(81 reference statements)
0
17
0
Order By: Relevance
“…As recently postulated (Vedal et al , 2013), combining combustion-source gases from fresh emissions with aged or secondary particles may enhance particle toxicity. Furthermore, we have confirmed the clinical relevance of diesel-induced serum bioactivity in human studies, showing not only induction of genes used in the present study (IL-8, ICAM-1, VCAM-1), but also a more complete microarray analysis of the endothelial cell response to plasma post-exposure (Channell et al ., 2012; Schisler et al ., 2015). The microarray analysis noted induction of more global inflammatory pathways in the endothelial cells treated with plasma post-diesel exposure, as well as induction of transcription factors previously unassociated with air pollution effects, including FOXO4, FOXF2, and TCF3 (Schisler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As recently postulated (Vedal et al , 2013), combining combustion-source gases from fresh emissions with aged or secondary particles may enhance particle toxicity. Furthermore, we have confirmed the clinical relevance of diesel-induced serum bioactivity in human studies, showing not only induction of genes used in the present study (IL-8, ICAM-1, VCAM-1), but also a more complete microarray analysis of the endothelial cell response to plasma post-exposure (Channell et al ., 2012; Schisler et al ., 2015). The microarray analysis noted induction of more global inflammatory pathways in the endothelial cells treated with plasma post-diesel exposure, as well as induction of transcription factors previously unassociated with air pollution effects, including FOXO4, FOXF2, and TCF3 (Schisler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Furthermore, it has been reported that polyphenols (namely resveratrol), as a nutraceutical treatment, led to reduced serum inflammatory potential in healthy subjects, as compared with placebo. 15 Such studies are coherent with animal toxicological research showing that the inhalation of various toxicants, including gases and particles, leads to inflammatory and antidilatory alterations in the serum composition.…”
Section: Introductionmentioning
confidence: 99%
“…MVE exposure induced several factors reflective of oxidative stress (oxidized glutathione, 13-HODE, 9-HODE) and altered fatty acid metabolism. In recent human and rodent studies, inhalation exposure to a wide variety of pollutants renders a pro-inflammatory bioactivity in the serum that can cause induction of inflammatory genes in cultured endothelial cells or impair vasodilation in isolated arteries (Aragon et al, 2015; Channell et al, 2012; Robertson et al, 2013; Schisler et al, 2015a). Metabolomic findings in the present study are consistent with serum alterations resulting from inhalation exposures, but it remains unclear if any specific alterations described herein cause this bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Diesel exhaust inhalation induced a pro-inflammatory activity in serum of healthy human subjects, in that the serum more potently elevated transcription of adhesion molecules and cytokines in cultured endothelial cells (Channell et al, 2012; Schisler et al, 2015b). More recently, we have noted that inhalation of ozone, which reacts completely in the lung and does not pass beyond the surfactant layer intact, led to changes in the serum that diminished endothelial-dependent vasodilation in rats and mice, and the scavenger receptor CD36 appears to have a prominent intermediary role (Paffett et al, 2015; Robertson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation